2014
DOI: 10.5195/jwsr.2014.564
|View full text |Cite
|
Sign up to set email alerts
|

The Core of the Apple: Degrees of Monopoly and Dark Value in Global Commodity Chains

Abstract: The capitalist world-economy takes the form of an iceberg. The most studied part which appears above the surface is supported by a huge underlying structure that is out of sight. Unlike the iceberg, the world-economy is a dynamic system based on flows of value from the underside toward the top. These include drains of surplus (expropriated value) We should think of the modern world-system as an iceberg economy in which uncosted labor and resources comprise the thicker submerged ice layers that are blocked fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
41
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 9 publications
0
41
0
2
Order By: Relevance
“…In terms of governance and control of the GVC, Gereffi (2014) suggested that this was related to the complexity of knowledge being transferred from lead companies to networks of suppliers. For example, although a company like Apple has an increasing impact on the dynamism of China's high tech exports, in terms of international trade statistics it remains quite invisible, even though its managers are involved in monitoring production in its supplier factories and suppliers in some cases use equipment purchased by Apple (Chan, Pun, & Selden, 2013;Clelland, 2014). This is not to suggest that there are not considerable levels of innovation in China, but much of it is incremental in nature and is related to the functions in which most ICT companies in China are specialising, such as assembly (Brandt & Thun, 2011;Breznitz & Murphree, 2011).…”
mentioning
confidence: 99%
“…In terms of governance and control of the GVC, Gereffi (2014) suggested that this was related to the complexity of knowledge being transferred from lead companies to networks of suppliers. For example, although a company like Apple has an increasing impact on the dynamism of China's high tech exports, in terms of international trade statistics it remains quite invisible, even though its managers are involved in monitoring production in its supplier factories and suppliers in some cases use equipment purchased by Apple (Chan, Pun, & Selden, 2013;Clelland, 2014). This is not to suggest that there are not considerable levels of innovation in China, but much of it is incremental in nature and is related to the functions in which most ICT companies in China are specialising, such as assembly (Brandt & Thun, 2011;Breznitz & Murphree, 2011).…”
mentioning
confidence: 99%
“…While scholars do not typically think this way, we have previously conceived global commodity chains to be chains of exploitation, grounded in stratified inequalities along racial, ethnic, class and gender lines (Clelland 2014(Clelland , 2015Dunaway 2012Dunaway , 2014. In short, these are the significant mechanisms through which capitalists structure and maintain ethnic/racial inequalities around the world, and they consist of thousands of sites at which battles against inequality must be waged if we are to effect worldwide change.…”
Section: Semiperipheral Exploitation Through Global Commodity Chainsmentioning
confidence: 99%
“…Compradors are those capitalists and state elites who do the frontline ethnic/racial exploitation within their own societies for their transnational class. One task of these cadres is to make production possible by draining both visible and hidden economic surpluses from ethnic communities (Clelland 2014). Through support from state elites, nonwestern capitalists super-exploit ethnic minorities in order to cement their positions in transnational capitalism (Clelland 2015).…”
Section: Semipheriperalization Of the Transnational Capitalist Classmentioning
confidence: 99%
See 1 more Smart Citation
“…Semiperipheral agriculture and industrialization are grounded in intense exploitation of ethnic minorities to secure low-paid and unpaid labor for national export agendas (Clelland 2014). …”
mentioning
confidence: 99%